Assessing service quality and its impact on patient experience and satisfaction in prosthetics and orthotics: a SERVQUAL-based cross-sectional study - Mahmoud Alfatafta; Nizar Alsubahi; Huda Alfatafta; Amneh Alshawabka; Anthony McGarry; Alaeddin Ahmad; Evelin Derkacs; Dorottya Varga; Bálint Molics (BMC Health Services Research)
Abstract Background Service quality plays a crucial role in shaping patient experience and satisfaction in prosthetic and orthotic services. However, limited research has examined the specific impact of SERVQUAL dimensions (Reliability, Assurance, Tangibility, Responsiveness, and Empathy) on patient satisfaction and patient experience in this field. This study aimed to assess the relationships between service quality, patient experience, and satisfaction, providing insights for healthcare improvement. Methods This cross-sectional study collected data from 307 patients receiving prosthetic and orthotic care at 14 centers across public, private, military, and NGO-operated facilities. A structured questionnaire based on the SERVQUAL model was administered, measuring patient experience, patient satisfaction, and service quality dimensions using a 5-point Likert scale. Structural equation modelling was conducted using IBM SPSS AMOS 28 to assess direct and indirect relationships among the study variables. Results The findings indicate that Responsiveness, Assurance, and Tangibility were the strongest predictors of patient experience and satisfaction (p < 0.001). Patient experience played a mediating role, reinforcing the importance of effective communication, timely service delivery, and competent care providers. Reliability significantly influenced PS (p < 0.001) but had no impact on PE (p = 0.386), while Empathy did not significantly affect PS (p = 0.311), suggesting that practical aspects such as device functionality and efficiency may be prioritized over emotional considerations in P&O care. Conclusions This study highlights the critical role of service quality in shaping patient experience and satisfaction in P&O services. Responsiveness, Assurance, and Tangibility should be prioritized to enhance patient-centered care. Policymakers should focus on standardized training programs, infrastructure improvements, and public-private partnerships to ensure accessible and high-quality P&O services globally. Future research should explore longitudinal effects of service quality on patient outcomes to further optimize healthcare delivery in this field.